Upakara Aci Usaba Sumbu Desa Pakraman Timbrah Sebagai Inspirasi Penciptaan Karya Seni Lukis - Silasana, I Putu Arya; Gulendra, I Wayan; Tjokropramono, I Gede Yosef (Program Studi Seni Murni ISI Bali, 2022)
the phenomenon of religious rituals in Timbrah Village named Aci Usaba Sumbu which has its own uniqueness from the facilities used in the ritual. Banten Sumbu which resembles a towering tower with all the attributes that adorn the banten and the banten be guling which is presented by the public en masse is an attraction or encouragement to present the visualization of the ceremony in a painting with certain references to achieve the goals and meanings expressed. The problem faced is how to process the visuals of the ceremony so that the meanings contained in a work can be realized and look attractive. The visualization stage in the work will apply the principles of art in the form of Balance, Proportion, Rhythm, Emphasis, and Unity. To answer related to the phenomena described, the method of creation is to carry out exploration, improvisation, formation and completion stages. From the ideas obtained, 6 works were created entitled: 1)